Efektivitas Waktu Pemberian dan Dosis Trichoderma harzianum dalam Menanggulangi Serangan Sclerotium rolfsii pada Tanaman Kedelai - Ochtaviana, Marghareta Bella; Jannah, Eka Nur; Novianto, Esna Dilli (Agrisintech (Journal of Agribusiness and Agrotechnology), 2025)
ABSTRACT The attack of Sclerotium rolfsii can significantly reduce soybean plant productivity, potentially leading to crop failure. Currently, farmers rely on fungicides to combat this issue. However, the continuous use of chemical control agents poses risks to the environment. Therefore, it is essential to explore alternative methods, such as utilizing biological agents like Trichoderma harzianum, which are more environmentally friendly. This study aims to analyze the effects of time application and the dosage of T. harzianum on reducing the incident of basal stem rot disease caused by S. rolfsii in soybean plants. This research was conducted from June to September 2024 at the Biotechnology and Plant Breeding Laboratory and the Bandongan Teaching Farm greenhouses at UNTIDAR. A Complete Randomized Block Design (3x4) was used in the study. The first factor was the application time of T. harzianum, namely 7 days before planting (T1), at planting time (T2), and 7 days after planting (T3). The second factor was the dosage of T. harzianum, which are 0, 225, 300, and 375 g/polybag. All data were analyzed with ANOVA, while the any significance tested further with orthogonal polynomials. Results indicated that applying T. harzianum 7 days before planting at a dosage of 375 g/polybag effectively reduced both the intensity of fungal attacks and the incidence of the disease. This timing and dosage combination also increased the effectiveness of the control measures and the height of the soybean plants. The interaction between the timing and dosage had a positive impact on reducing disease severity and enhancing control efficacy. T. harzianum demonstrated antagonistic activity against S. rolfsii, likely due to competition for space and nutrients, as well as antibiotic produced by the antagonistic fungi. In conclusion, this study suggests that T. harzianum can effectively inhibit S. rolfsii attacks on soybean plants when applied at the appropriate time and dosage. ABSTRAK Serangan jamur Sclerotium rolfsii pada tanaman kedelai dapat menyebabkan penurunan produktivitas tanaman hingga gagal panen. Saat ini, petani menggunakan fungisida untuk mengatasi hal tersebut. Namun demikian, penggunaan agen pengendali kimiawi secara terus menerus berdampak pada kerusakan lingkungan, sehingga perlu dicari alternatif lain dengan memanfaatkan agensia hayati seperti Trichoderma harzianum yang lebih ramah lingkungan. Penelitian ini bertujuan untuk mempelajari pengaruh waktu pemberian dan dosis T. harzianum terhadap serangan jamur S. rolfsii penyebab penyakit busuk pangkal batang pada tanaman kedelai. Penelitian telah dilaksanakan pada bulan Juni-September 2024 di Laboratorium Bioteknologi dan Pemuliaan Tanaman dan greenhouse Bandongan Teaching Farm UNTIDAR. Rancangan Acak Kelompok Lengkap (3 x 4) digunakan pada penelitian ini. Faktor pertama yaitu waktu pemberian T. harzianum 7 hari sebelum tanam (T1), saat tanam (T2), dan 7 hari setelah tanam (T3). Faktor kedua adalah dosis T. harzianum yaitu 0, 225, 300 dan 375 g/polybag. Hasil penelitian menunjukkan bahwa waktu pemberian T. harzianum 7 hari sebelum tanam dan dosis 375 g/polybag berpengaruh menurunkan intensitas serangan dan kejadian penyakit serta meningkatkan efektivitas pengendalian dan tinggi tanaman kedelai. Interaksi antar kedua faktor berpengaruh menurunkan intensitas serangan dan kejadian penyakit serta meningkatkan efektivitas pengendalian. T. harzianum memiliki aktivitas antagonisme terhadap patogen S. rolfsii. Diduga terjadi persaingan ruang dan nutrisi, serta aktivitas antibiosis dari jamur antagonis. Dari penelitian ini dapat disimpulkan bahwa T. harzianum mampu menghambat serangan jamur S. rolfsii pada tanaman kedelai dengan waktu pemberian dan dosis yang tepat.